Thermoformed Containers for Packaging and Frozen Storage of Fish (Scotnberomorus guttatus) Curry - T.K., Srinivasa Gopal; A.C., Joseph; T.S.G., Iyer; P.V., Prabhu (Fishery Technology, 2025)
Seer fish (Scomberomorus guttatus) curry was dispensed in 150 to 174 g lots in thermoformed containers of 294 and 328 cm3 volume made from Polystyrene (PS) and Polyvinyl chloride (PVC) respectively and top of the tray was heat sealed using plain Polyester film laminated with low density polythene. The trays were stored at -20Â±2oC and the properties of the curry packed in PS and PVC trays were compared. The curry remained in good condition for 26 weeks in these thermoformed containers. Overall migration residues in both the trays studied were within the limits specified by the Bureau of Indian Standards and the U.S. Food and Drug Administration.